2010
DOI: 10.3109/10611861003663523
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive chitosan microspheres of carvedilol for nasal administration

Abstract: The aim of the present study was to develop and characterize chitosan mucoadhesive microspheres of carvedilol (CRV) for nasal delivery to improve bioavailability for treatment of hypertension and angina pectoris. The microspheres were prepared by emulsification-cross-linking method and evaluated for size, shape, entrapment efficiency (EE), in vitro mucoadhesion, in vitro drug release, differential scanning calorimetry (DSC) and X-ray diffraction (XRD). The mucoadhesive properties were also evaluated by Freundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 33 publications
4
39
0
1
Order By: Relevance
“…This obviously exhibits significant radioactivity aggregation in the brain after intranasal administration for a desired period and these results were in great concurrence with the past discoveries (Patil et al, 2010). Results of gamma scintigraphy study revealed that liposomal dispersion shows more accumulated 99m Tc into the brain in comparison with simple dispersion.…”
Section: Gamma Scintigraphysupporting
confidence: 75%
“…This obviously exhibits significant radioactivity aggregation in the brain after intranasal administration for a desired period and these results were in great concurrence with the past discoveries (Patil et al, 2010). Results of gamma scintigraphy study revealed that liposomal dispersion shows more accumulated 99m Tc into the brain in comparison with simple dispersion.…”
Section: Gamma Scintigraphysupporting
confidence: 75%
“…Recently, the use of polymeric carriers in formulations of therapeutic drug delivery systems, such as gelatin (TabataIkada 1989;Tabata et al 1999;Sakakibara et al 2002), chitosan (Guo et al 2010;Patil et al 2010), Poly(lactide-co-glycolide) (PLGA) (TsungBurgess 2001) and poly(lactic acid) (PLA) (ShiveAnderson 1997), has gained widespread application, due to their advantage of being biodegradable and biocompatible (Tuncay et al 2000). Among the various polymeric carrier systems, PLGA microspheres have been shown to be very suitable…”
Section: Introductionmentioning
confidence: 99%
“…After 24 h, the filtrate was diluted with phosphate buffer pH 6.4 and final solution was assayed spectrophotometrically at 232 nm for drug content. [16,17,18] Estimated drug content % Entrapment efficiency = ×100 Theoretical drug content…”
Section: Drug Entrapment Efficiencymentioning
confidence: 99%
“…At predetermined time interval of 0, 1, 2, 3, 4, 5, 6, 7, and 8 h, 1ml of sample was withdrawn, diluted, filtered, and analyzed by UV Visible spectrophotometer at 232 nm. [11,24,26,29,30] Fourier transforms infrared spectroscopy…”
Section: Analysis Of In Vitro Drug Release Kinetics and Mechanismmentioning
confidence: 99%